Roles of coach’s behaviour in affecting the prosocial and antisocial behaviour in athletes: a systematic review / Fariha Mohammad Fazilah, Jamilah Ahmad Radzi, Al Hafiz Abu Bakar and Ahmad Fikri Mohd Kassim - Fazilah, Fariha Mohammad; Radzi, Jamilah Ahmad; Abu Bakar, Al Hafiz; Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, 2023)
Prosocial and antisocial behaviour have been utilized in sports exploration to allude proactive and inhibitive profound quality, whilst, individually with low degrees of antisocial behaviour reflecting inhibitive ethical quality. A wide range of coaching conduct affects the behavioural results of athletes. Athletes usually endorse sporting behaviour when coaches generate a mastery climate that accentuates learning, effort and enhancement as keys to success. Contrary to a performance climate that emphasises outperforming others and winning. Therefore, the primary aim of this study is to examine the past literature about the roles of the coach’s behaviour in affecting the prosocial and antisocial behaviour in athletes. This study carried out an extensive online assessment of the data source (Scopus and Web of Science) and a conference scheduled of possibly related papers. The search methods were restricted to studies published in English with full-text availability. A total of 39 studies were chosen from 58 total records. However, a few studies accepted for the review, of which two were selected in qualitative synthesis and thirteen studies selected in the quantitative synthesis. In these two published types of research, we filter out the data (Scopus and Web of Science). As a result, a sample of 15 dissertations and theses selected for systematic quality analysis. The findings systematically evaluate cross-sectional observation-based studies the coach-athlete relationship may be critically significant for thoughtful athletes’ moral behavior in sport. Thus, as a result, it is vital that the coaching approach may focus on the importance of establishing a sports environment that promotes positive behaviors and enables athletes to acquire a feeling of responsibility and self-regulation.